Economic study on the effectiveness of photovoltaic street lighting in Universiti Teknologi Malaysia - Ab. Rahman, Hasimah; Hassan, M. Y.; Majid, M. S.; Mohd. Nor, Kamarudin; Atan, N. A. (2008)
This paper presents a feasibility study of installing the photovoltaic street lighting at 15 sites in the Univeristi Teknologi Malaysia (UTM), Johor Bahru campus. A comparative economic analysis on the actual electricity bill for UTM with and without photovoltaic (PV) street lighting was performed. The finding shows that there is approximately 1% reduction in the electricity bill with the pay back period of 7.5 years for the complete installation of PV system. In selecting the suitable module for the PV street lighting, two types of PV technologies; amorphous Silicon and monocrystalline Silicon were studied and compared.